2014
DOI: 10.1007/s12600-013-0379-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of some alternative methods to chemical control in controlling aphids (Hemiptera: Sternorrhyncha) and their side effects on natural enemies on young Moroccan citrus groves

Abstract: Aphid control in Moroccan citrus orchards is based mainly on carbamate and neonicotinoid sprays, especially methomyl and imidacloprid. The extensive use of these insecticides may have side effects on natural enemies and environment quality and raises human health concerns. This research aimed to assess the control of aphids with insecticidal soap, kaolin and augmentative biological control using the indigenous predator Adalia decempunctata L. (Coleoptera: Coccinellidae). The insecticides were applied and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…
http://www.eje.cz Citrus tristeza closterovirus (Closterovirus: Closteroviridae) (Ayazpour et al, 2013). Chemical control is the main method used to control citrus aphids (Smaili et al, 2014). However, excessive use of insecticides reduces natural enemy populations and leads to resistance of the aphids to many common insecticides.
…”
mentioning
confidence: 99%
“…
http://www.eje.cz Citrus tristeza closterovirus (Closterovirus: Closteroviridae) (Ayazpour et al, 2013). Chemical control is the main method used to control citrus aphids (Smaili et al, 2014). However, excessive use of insecticides reduces natural enemy populations and leads to resistance of the aphids to many common insecticides.
…”
mentioning
confidence: 99%
“…Regarding insecticidal soaps, some detrimental effects of different formulations have also been registered both in field and laboratory conditions on beneficial non-target arthropods belonging to Acari (Phytoseiidae), Coleoptera (Coccinellidae), Neuroptera (Chrysopidae) and Hymenoptera (Eulophidae, Braconidae) (Oetting & Latimer, 1995;Smith & Krischik, 2000;Kraiss & Cullen, 2008;Raudonis et al, 2010;Hall & Richardson, 2013;Smaili et al, 2014). In addition, negative effects on predators and parasitoids have been reported for plant essential oils.…”
Section: Discussionmentioning
confidence: 99%
“…No negative effect of insecticidal soaps on natural enemies have been reported in many studies (Natarajan, 1990;Bigler & Waldburger, 1994;Jacas Miret & GarcĂ­a-MarĂ­, 2001; Karagounis et al, 2006;Jansen et al, 2010). However, in others, negative effects of soaps applications were found on some groups of natural enemies (Oetting & Latimer, 1995;Smith & Krischik, 2000;Stansly et al, 2002;Kraiss & Cullen, 2008;Raudonis et al, 2010;Hall & Richardson, 2013;Smaili et al, 2014). In the case of essential oils, again some studies reported no negative effect on natural enemies (Echegaray & Cloyd, 2012;GonzĂĄlez et al, 2013), but some detrimental effects have been also reported (Momen & Amer, 1999;Amer & Momen, 2002;Choi et al, 2004;Bostanian et al, 2005;Huignard et al, 2008;Cloyd et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…The negative impact caused by pests reduces the quantity and quality of production. Indeed, spider mites, aphids, medflies, and diaspine scales are pests of primary economic importance [ 8 , 9 ]. When conditions are favorable and in the absence of adequate methods of control, significant damage is often observed on the fruits, twigs, leaves, and young shoots of citrus [ 10 ].…”
Section: Introductionmentioning
confidence: 99%